The Factors Affecting Academic Administration in Schools Under Chachoengsao Secondary Educational Service Area Office - Chuahorm, Chanasanun; Khongthiang, Somsak; Prasertsin, Ujsara (Journal of Graduate MCU KhonKaen Campus, 2025)
The purposes of this research were 1) to study the level of factors influencing academic administration in schools, 2) to study the level of effectiveness in academic administration in schools, 3) to generate predictive equations for academic administration in schools, 4) to study the guideline for enhancing academic administration in schools under the jurisdiction of the Secondary Educational Service Area Office, Chachoengsao. A mixed-method research approach was employed, divided into two phases. In Phase 1, the sample group consisted of 351 school administrators and teachers, selected through stratified random sampling. Data were collected using a rating-scale questionnaire and analyzed using percentage, mean, standard deviation, Pearson's correlation coefficient, and stepwise multiple regression analysis. In Phase 2, the sample group included seven school administrators and teachers. Data were collected through semi-structured interviews and analyzed using interpretation and content analysis. The findings were as follows: 1) The factors affecting the effectiveness of academic management in schools are generally at a high level. 2) The effectiveness of academic management in schools is generally at a high level. 3) The factors that significantly affect the effectiveness of academic management in schools at the .01 level are three variables. These are ranked by their influence from most to least as follows: leadership, teachers, and school facilities. The regression equation in raw score form is Y = 1.255+ 0.328 (X1) + 0.306X2) + 0.130(X4) The regression equation in standardized score form is Zy = 0.360(X1) + 0.304(X2) + 0.190(X4) 4) The guideline to enhance the effectiveness of academic administration in schools is divided into four main approaches as follows: 1) student quality: schools recognize and reward students with outstanding academic performance, 2) teacher educational management: teachers are encouraged to participate in training programs, 3) community participation: parents and community members are encouraged to actively engage in school activities, 4) administrative management: school administrators must clearly define the goals and objectives of academic operations.